PO-26 - Whole blood rotational thromboelastometry (ROTEM) to detect hypercoagulability in patients with myeloproliferative neoplasms (MPN). Issue 140 (April 2016) - Giaccherini, C.; Verzeroli, C.; Marchetti, M.; Gamba, S.; Piras, F.; Russo, L.; Tessarolo, S.; Vignoli, A.; Finazzi, G.; Rambaldi, A.; Falanga, A.
Abstract : Introduction: Essential Thrombocythemia (ET) and Polycythemia Vera (PV) are two MPNs characterized by a "clonal" overproduction of one or more blood cell lines, hypercoagulability, and an increased incidence of thrombosis. ROTEM is a point of care global coagulation assay performed in whole blood, able to evaluate platelets and fibrinogen contributions to the clotting process. Until now few studies evaluated the thromboelastometry profile of MPN patients. Aim: This study assess the feasibility of using ROTEM to characterize the prothrombotic state of MPN patients and to evaluate whether the thromboelastometry profile varies according to mutational status and/or treatment, and is influenced by hemocromocytometric parameters. Materials and Methods: Venous blood samples were collected from 39 ET and 23 PV patients upon informed consent. Analysis was performed using INTEM and EXTEM reagents, to evaluate the intrinsic and extrinsic pathway, respectively. Maximum clot firmness (MCF, [mm]), which reflects the maximum tensile strength of the thrombus, clotting formation time (CFT [sec]), namely the time that clot takes to increase from 2 to 20 mm above baseline, and clotting time (CT [sec]), the time to clot initiation, were recorded. Nineteen healthy subjects acted as a control group. Results: ROTEM analysis showed a hypercoagulable profile in MPN patients, who had shorter CFT and higher MCF compared to controls, both with EXTEM and INTEM reagents; no differences were observed in CT parameters. Platelet count was significantly higher in patients compared to controls (p < 0.01). In patients, a strong statistically significant (p < 0.01) correlation was found between platelet count, and MCF [r = 0.650 (ET), r = 0.601 (PV)] or CFT [r = − 0.641 (ET), r = − 0.558 (PV)]. Multivariate analysis, according to blood cell counts, showed that only platelet count was independently associated to ROTEM results. To correct for platelet differences, a ratio between MCF and the respective platelet value (rMCF) was created. Interestingly, rMCF was significantly lower in patients compared to controls (p < 0.01), suggesting a weaker clot formation potential of patients' samples. Furthermore, rMCF was lower in ET compared to PV (p < 0.05), and in calreticulin-positive subjects (p < 0.05), while was higher in patients under cytoreductive therapy (Hydroxyurea) (p = ns). Conclusions: This study confirms, by the ROTEM evaluation, the occurrence of a hypercoagulable state in ET and PV patients. In addition, the ROTEM parameters are significantly influenced by the platelet count. Finally, MCF values corrected for platelet count reveal a lower platelet reactivity in MPN patients, confirming the hypothesis that platelet function is exhausted upon clotting activation. Acknowledgement: Project funded by "AIRC-IG2013" grant Nr. 14505 from the "Italian Association for Cancer Research" (A.I.R.C.).